Plasmapheresis in the Treatment of Refractory Myoclonic Status. A Case Report - Gutierrez-Gutierrez Judit (Sciendo, 2021)
A case of myoclonic status treated with plasmapheresis in a patient of 63 years of age who was admitted to a Spanish intensive care unit is reported. The patient showed clinical and radiological evidence of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection; molecular tests did not verify this.